Trends in temperature and rain change in Iraq and its future projections - Al-Budeiri, Ahmed Lafta (Al-Adab Journal, 2021)
The current study provides a spatial and temporal assessment of temperature trends and rainfall in Iraq for the period from 1979 to 2018, based on the data of the Iraqi Meteorological Organization, and the use of the Mann- Kendall test at significance levels (0.01 -0.05), in addition to assessing the rates of change using the Sen’s test. The results of the study revealed an increase in the lowest temperatures in the study period in all seasons of the year, and the summer season recorded faster trends towards warmth (exceeding 3 ° C during the study period) in some monitoring stations, as in the stations of Khanaqin and Najaf. The results of the rain trend analysis have clear spatial and temporal variations, taking into account that most of the stations were characterized by a decrease in the amounts of rain during the spring and autumn seasons and at the annual level as well, while the autumn recorded an increase in the amounts of rain in most of the stations, and the study was concerned with what was mentioned in the evaluation of future changes In terms of temperatures and rainfall, depending on the data derived from the Coordinated Regional Downscaling Experiment (CORDEX), through two models, and two scenarios (RCP4.5 & RCP8.5), we have adopted the assessment of the projections. Climate acceptability on the comparison of climate forecasts for the future period (2021-2060) for the base period (1979-2018) and the results showed that the minimum temperatures for the RCP4.5 moderate scenario will increase by (-1.1 1.7) ° C during the next four decades, while it is expected that Maximum temperatures are higher than current rates by (1.6 -2.7) ° C, Compared to the current climate, according to the high scenario RCP8.5, rainfall will decrease by (58-69) in most parts of Iraq according to scenarios RCP4.5 RCP8.5, particularly the southern regions, and accordingly future climate changes will add more environmental and economic pressures in Iraq, particularly the agricultural production sectors, water resources, energy consumption, etc., which requires the development of policies and strategies for adaptation to climate change.